Trauma and fear in Australian midwives. Issue 1 (February 2019) - Toohill, J.; Fenwick, J.; Sidebotham, M.; Gamble, J.; Creedy, D.K.
Abstract: Background: Relatively little is known about the extent of trauma and birth-related fear in midwives and how this might affect practice. Aim: (1) Determine prevalence of birth related trauma and fear in midwives and associations with midwives' confidence to advise women during pregnancy of their birth options and to provide care in labour. (2) Describe midwives' experiences of birth related trauma and/or fear. Method: A mixed methods design. A convenience sample of midwives (n = 249) completed an anonymous online survey. Descriptive and inferential statistics were used to analyse the quantitative data. Latent content analysis was used to extrapolate meaning from the 170 midwives who wrote about their experiences of personal and/or professional trauma. Results: The majority of midwives (93.6%) reported professional (n = 199, 85.4%) and/or personal (n = 97, 41.6%) traumatic birth experiences. Eight percent (n = 20) reported being highly fearful of birth. Trauma was not associated with practice concerns but fear was. Midwives categorised as having 'high fear' reported more practice concerns (Med 23.5, n = 20) than midwives with 'low fear' (Med 8, n = 212) (U = 1396, z = −3.79, p < 0.001, r = 0.24). Reasons for personal trauma included experiencing assault, intervention and stillbirth. Professional trauma related to both witnessing and experiencing disrespectful care and subsequently feeling complicit in the provision of poor care. Feeling unsupported in the workplace and fearing litigation intensified trauma. Conclusion: High fear was associated with lower confidence to support childbearing women. Fear and trauma in midwives warrants further investigation to better understand the impact on professional practice.